Hubungan Intensitas Penggunaan Tiktok dengan Etika Belajar Mahasiswa Rumpun Pendidikan Ilmu Pengetahuan Sosial FKIP ULM - Nur Rahimah; Rabiatul Adawiah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to measure the relationship between TikTok usage intensity (based on frequency, duration, purpose, and user engagement) and student learning ethics in the Social Science Education Department (PIPS) FKIP ULM.. The population encompassed all active students in the Social Science Education Department (PIPS), with a sample size of 165 respondents selected via random sampling techniqueThe statistical hypothesis testing results showed a significance value of 0.001 with a correlation coefficient of 0.613. This primary finding proves a positive and significant relationship in the strong category between TikTok usage intensity and student learning ethics. This outcome indicates that higher platform engagement aligns linearly with respondents' strengthened understanding of learning integrity values continuously within their daily campus life. Based on the comprehensive findings of this research, students are advised to maintain learning consistency and implement wise time management in social media platforms.